Profiling the autoantibody repertoire reveals autoantibodies associated with mild cognitive impairment and dementia - Ehtewish, Hanan; Mesleh, Areej; Ponirakis, Georgios; Lennard, Katie; Al Hamad, Hanadi; Chandran, Mani; Parray, Aijaz; Abdesselem, Houari; Wijten, Patrick; Decock, Julie; Alajez, Nehad M.; Ramadan, Marwan; et al. (Frontiers in Neurology, 2023)
Background: Dementia is a debilitating neurological disease affecting millions of people worldwide. The exact mechanisms underlying the initiation and progression of the disease remain to be fully defined. There is an increasing body of evidence for the role of immune dysregulation in the pathogenesis of dementia, where blood-borne autoimmune antibodies have been studied as potential markers associated with pathological mechanisms of dementia.Methods: This study included plasma from 50 cognitively normal individuals, 55 subjects with MCI (mild cognitive impairment), and 22 subjects with dementia. Autoantibody profiling for more than 1600 antigens was performed using a high throughput microarray platform to identify differentially expressed autoantibodies in MCI and dementia.The differential expression analysis identified 33 significantly altered autoantibodies in the plasma of patients with dementia compared to cognitively normal subjects, and 38 significantly altered autoantibodies in the plasma of patients with dementia compared to subjects with MCI. And 20 proteins had significantly altered autoantibody responses in MCI compared to cognitively normal individuals. Five autoantibodies were commonly dysregulated in both dementia and MCI, including anti-CAMK2A, CKS1B, ETS2, MAP4, and NUDT2. Plasma levels of anti-ODF3, E6, S100P, and ARHGDIG correlated negatively with the cognitive performance scores (MoCA) (r 2 -0.56 to -0.42, pvalue < 0.001). Additionally, several proteins targeted by autoantibodies dysregulated in dementia were significantly enriched in the neurotrophin signalling pathway, axon guidance, cholinergic synapse, long-term potentiation, apoptosis, glycolysis and gluconeogenesis.We have shown multiple dysregulated autoantibodies in the plasma of subjects with MCI and dementia. The corresponding proteins for these autoantibodies are involved in neurodegenerative pathways, suggesting a potential impact of autoimmunity on the aetiology of dementia and the possible benefit for future therapeutic approaches. Further investigations are warranted to validate our findings.